Macroeconomic Factors Affecting Natural Gas Export Management - Wildan, Muhammad Alkirom; Imron, Mochamad Ali; Siswati, Endang; Rosyafah, Siti (International Journal of Energy Economics and Policy, 2020)
Indonesia as a rich country with its natural resources to be one of the countries in the world to play an active role in increasing international trade flows. One of the energy which is very beneficial to human life is a natural gas. The use of this energy will meet to household needs and another important needs for industry. The data presented is a secondary data in the form of time series for 22 years, a period 1995-2017. The variables of this study are domestic consumption, exchange rate, international price, and GDP per capita of the importing country. Then, the analytical method used is Auto-regressive Distributed Lag (ARDL). The results of the analysis shown that in the short term all variables such as domestic consumption, exchange rates, natural gas prices and GDP per capita significantly influence to volume of natural gas exports. While in the long run term, the results which is the same as the short run, that is, all the independent variables such as domestic consumption, the exchange rate, international prices and GDP per capita have a significant effect on the volume of natural gas exports. Keywords: Gas consumption, Exchange rate, Natural gas, Gross domestic product JEL Classifications: E2, E6, Q4 DOI: https://doi.org/10.32479/ijeep.9911